Diffuse “vertebra-within-vertebra” appearance at the adult age due to biphosphonate (pamidronate) administration during early adolescence - B Coulier (Journal of the Belgian Society of Radiology, 2011)
We report a rare case of diffuse alteration of the vertebral bony structure fortuitously found in a 20-year-old patient and essentially characterized by an impressive “vertebra-within-vertebra” appearance. This aspect was found being the result of an unusual use of intravenous perfusions of biphosphonate (Pamidronate) during early adolescence for reflex sympathetic dystrophy after tibial fracture. The clinical applications of biphosphonates are briefly reminded and the physiopathology of the induced bone changes is explained.